The Effect of Different Sport Stress Coping Styles on Sources of Acute Stress and Salivary Cortisol in Wrestlers - Mohamad Hosein Ghahramani; Mohamad Ali Besharat; Seyyed Reza Attarzadeh Hosseini; Ali Akbarnejad (University of Tehran, 2015)
Coping style is one of the substantial factors influencing sport achievements insport competitions. The main aim of the present study was to examine the effect ofsport stress coping styles on sources of acute stress and salivary cortisol inwrestlers. With regard to the criteria and variables of this study, 30 out of 270active national wrestlers participated according to the cut-off point of coping stylesquestionnaire in two approach and avoidant coping groups. The participants wereasked to complete Sources of wrestling acute stress questionnaire and to collect thesaliva to measure salivary cortisol levels. Multivariate analysis of variance resultsindicated that sources of acute stress were significantly higher in approach copingwrestlers than avoidant coping group (P=0.001). Also, salivary cortisol level wassignificantly lower in avoidant coping group than the approach coping group(P=0.012). According to the results, different stress coping styles influencedperceived stress of acute stress and salivary cortisol levels in wrestlers. Thefindings of this study can be used in instruction of different sport stress copingstyles in wrestlers in order to reduce their mental pressure in the competitions.